PENGGUNAAN APLIKASI PEMBAYARAN DIGITAL PADA MAHASISWA FEB UPN VETERAN JAKARTA - Rifandini Rahyanti, (2022)
In the growing industry 4.0, modern society has been rewarded with the benefits of daily living. New innovations are surging through the digital age, making all human activities increasingly efficient, safe, and comfortable. One is the emergence of a digital or electronic payment app that allows users to make noncash transactions at any time or place. Currently there are various digital payment applications from different companies that students can select. Each application offers its own advantage. The study is conducted to know how the use of the digital payment app affects consumer behavior and to know the reasons behind the use of digital payment applications especially on students of FEB UPN Veteran students Jakarta. According to questionnaires, showing a digital payment application to be a preferred choice by students, but the ease with which these digital payment services are able to affect consumer behavior on the part of the user. This consumer behavior stems from the many conveniences and promo applications provided for digital payment.